Effects of Public Posting and Goal Setting on Team Performance in a Residential Setting. (3rd June 2016) - Perrin, Christopher J.; Fredrick, Amy; Klick, Sheila
Abstract : Treatment integrity has been shown to be of critical importance in behavioral programming. The extent to which tasks are completed as designed often has a direct effect on the quality of care provided to clients. Most research on treatment integrity has focused on implementation of interventions. The current study used a multiple baseline design across behaviors to evaluate the effects of public posting of team performance data and goal setting on data collection by direct‐care staff. Results of the current study suggest that public posting and goal setting may be effective strategies to improve staff data collection. Copyright © 2016 John Wiley & Sons, Ltd.